Validation of the Turkish adaptation of FACETS-OF-PPC: a multidimensional outcome measure for pediatric palliative care - Oztek Celebi, Fatma Zehra; Bozdag, Yasemin; Boybeyi, Songul Deniz; Oguz, Melahat Melek; Altinel Acoglu, Esma; Senel, Saliha; Sahin, Sanliay (Frontiers in Oncology, 2025)
IntroductionThis study aims to validate the Turkish version of the Family-Centered Multidimensional Outcome Measure for Pediatric Palliative Care (FACETS-OF-PPC), originally developed in Germany for children with severe neurological impairments and their families.MethodsThe FACETS-OF-PPC was translated and culturally adapted following the World Health Organization's guidelines. Following expert reviews and pilot testing, the final version was completed and implemented between February and December 2021 at a pediatric palliative care center in Türkiye. Participants included family members and healthcare professionals closely involved with the patients. Exclusion criteria were age over 18, end-of-life stage, or non-Turkish speakers. Confirmatory factor analysis was conducted to evaluate the factorial validity.Results and discussionThe study analyzed 102 responses (51 parents, 51 healthcare professionals), revealing suboptimal model fit (X2/df = 2.29; CFI=0.805; TLI=0.757; SRMR=0.109; RMSEA = 0.114). Internal consistency was adequate for the "normalcy" (w = 0.87) and "caregiver competencies" (w = 0.86) scales, but insufficient for "child’s social participation" (w = 0.51), "social support" (w = 0.20), and "coping with the disease" (w = 0.50). While the Turkish version of FACETS-OF-PPC showed reliable results for certain dimensions, cultural differences and the small sample size likely affected the overall validity, suggesting the need for further refinement.